Do We Need to Stabilize All Reduced Metaphyseal Both-bone Forearm Fractures in Children with K-wires?. Issue 2 (February 2022) - Diederix, Leon W.; Roth, Kasper C.; Edomskis, Pim P.; Musters, Linde; Allema, Jan Hein; Kraan, Gerald A.; Reijman, Max; Colaris, Joost W.
Abstract: Background: Short-term follow-up studies have shown that reduced metaphyseal both-bone forearm fractures in children should be treated with K-wires to prevent redisplacement and inferior functional results. Minimum 5-year follow-up studies are limited. Range of motion, patient-reported outcome measures, and radiographic parameters at minimum 5-year follow-up should be evaluated because they could change insights into how to treat pediatric metaphyseal forearm fractures. Questions/purposes: (1) Does K-wire stabilization of reduced metaphyseal both-bone forearm fractures in children provide better forearm rotation at minimum 5-year follow-up? (2) Do malunions (untreated redisplaced fractures) of reduced metaphyseal both-bone forearm fractures in children induce worse functional results? (3) Which factors lead to limited forearm rotation at minimum 5-year follow-up? Methods: We analyzed the extended minimum 5-year follow-up of a randomized controlled trial in which children with a reduced metaphyseal both-bone forearm fracture were randomized to either an above-elbow cast (casting group) or fixation with K-wires and an above-elbow cast (K-wire group). Between January 2006 and December 2010, 128 patients were included in the original randomized controlled trial: 67 in the casting group and 61 in the K-wire group. For the current study, based on an a priori calculation, it was determined that, with an anticipated mean limitation in prosupination (forearm rotation) of 7° ± 7° in the casting group and 3° ± 5° in the K-wire group, a power of 80% and a significance of 0.05, the two groups should consist of 50 patients each. Between January 2014 and May 2016, 82% (105 of 128) of patients were included, with a mean follow-up of 6.8 ± 1.4 years: 54 in the casting group and 51 in the K-wire group. At trauma, patients had a mean age of 9 ± 3 years and had mean angulations of the radius and ulna of 25° ± 14° and 23° ± 18°, respectively. The primary result was limitation in forearm rotation. Secondary outcome measures were radiologic assessment, patient-reported outcome measures (QuickDASH and ABILHAND-kids), handgrip strength, and VAS score for cosmetic appearance. Assessments were performed by the first author (unblinded). Multivariable logistic regression analysis was performed to analyze which factors led to a clinically relevant limitation in forearm rotation. Results: There was a mean limitation in forearm rotation of 5° ± 11° in the casting group and 5° ± 8° in the K-wire group, with a mean difference of 0.3° (95% CI -3° to 4°; p = 0.86). Malunions occurred more often in the casting group than in the K-wire group: 19% (13 of 67) versus 7% (4 of 61) with an odds ratio of 0.22 for K-wiring (95% CI 0.06 to 0.80; p = 0.02). In patients in whom a malunion occurred (malunion group), there was a mean limitation in forearm rotation of 6° ± 16° versus 5° ± 9° in patients who did not have a malunion (acceptable alignment group), with a mean difference 0.8° (95% CI -5° to 7°; p = 0.87). Factors associated with a limited forearm rotation ≥ 20° were a malunion after above-elbow casting (OR 5.2 [95% CI 1.0 to 27]; p = 0.045) and a refracture (OR 7.1 [95% CI 1.4 to 37]; p = 0.02). Conclusion: At a minimum of 5 years after injury, in children with a reduced metaphyseal both-bone forearm fracture, there were no differences in forearm rotation, patient-reported outcome measures, or radiographic parameters between patients treated with only an above-elbow cast compared with those treated with additional K-wire fixation. Redisplacements occurred more often if treated by an above-elbow cast alone. If fracture redisplacement is not treated promptly, this leads to a malunion, which is a risk factor for a clinically relevant (≥ 20°) limitation in forearm rotation at minimum 5-year follow-up. Children with metaphyseal both-bone forearm fractures can be treated with closed reduction and casting without additional K-wire fixation. Nevertheless, a clinician should inform parents and patient about the high risk of fracture redisplacement (and therefore malunion), with risk for limited forearm rotation if left untreated. Weekly radiographic monitoring is essential. If redisplacement occurs, remanipulation and fixation with K-wires should be considered based on gender, age, and direction of angulation. Future research is required to establish the influence of (skeletal) age, gender, and the direction of malunion angulation on clinical outcome. Level of Evidence: Level I, therapeutic study.